2018
DOI: 10.1038/s41418-018-0120-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced microRNA-191 contributes to hepatic ischemia/reperfusion injury through the ZONAB/Cyclin D1 axis

Abstract: Hepatic ischemia/reperfusion injury (IRI) is a common cause of morbidity and mortality in liver transplantation settings and involves severe cell death and inflammatory responses. MicroRNA-191 has recently been reported to be abnormally expressed in hepatocellular carcinoma and other liver diseases in the regulation of important cellular processes. However, little is known about its function and molecular mechanism in IRI. Here, we demonstrate that miR-191 is significantly upregulated in a cultured cell line d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Knockdown of miR-191 could reduce the infarction area induced by MCAO in rats and promote proliferation, migration, tube formation and spheroid sprouting in HUVEC. Our results complement nicely with a previous report showing that knockout of miR-191 reduced hepatic ischemia-reperfusion injury through inhibiting inflammatory responses and cell death [41]. Another study also showed that up-regulated miR-191 participated in renal ischemia-reperfusion injury via inducing apoptosis of renal tubular epithelial cells [42].…”
Section: Discussionsupporting
confidence: 91%
“…Knockdown of miR-191 could reduce the infarction area induced by MCAO in rats and promote proliferation, migration, tube formation and spheroid sprouting in HUVEC. Our results complement nicely with a previous report showing that knockout of miR-191 reduced hepatic ischemia-reperfusion injury through inhibiting inflammatory responses and cell death [41]. Another study also showed that up-regulated miR-191 participated in renal ischemia-reperfusion injury via inducing apoptosis of renal tubular epithelial cells [42].…”
Section: Discussionsupporting
confidence: 91%
“…Hepatic ischemia-reperfusion (IR) injury induces high morbidity and mortality of patients following liver resection and transplantations 1 , 2 As reported, it is the leading cause of liver dysfunction and failure after liver surgery or transplantation, and satisfactory strategies to ameliorate hepatic IR injury are limited. 3 Emerging studies have unraveled the involvement of significant cell death and inflammatory responses 4 and oxidative stress and tissue damage 5 in hepatic IR injury. Interestingly, NLRP3 inflammasome activation has been reported to possess a critical function in hepatic IR injury.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlethal segmental (70%) liver ischemia was performed as previously described. ( 20 ) Mice were sacrificed after 1 hour of ischemia and 6 hours of reperfusion. The isolation of hepatocytes from IR‐model mice livers was briefly summarized as the livers were excised, minced, and strained through a steel mesh, then purified by low‐speed centrifugation (3 times at 50 g for 5 minutes each).…”
Section: Methodsmentioning
confidence: 99%